An integration of multiple student engagement dimensions into a single measure and validity-based studies - Moreira, Paulo (2022)
Student engagement is typically regarded as being a multidimensional construct, but there remains no clear consensus about its precise conceptualization. Several current measures of student engagement are limited by their omission of relevant dimensions and/or poor correspondence between dimension labels and item content. To address these limitations, we integrated dimensions from two validated student engagement instruments, each with different approaches to the dimensionality of student engagement, into a single measure and assessed its psychometric properties. We concluded from factor analyses that this scale captures seven distinct-yet-related engagement dimensions, including students’ perceptions of contextual influences, which load on a global higher-order student engagement construct. Structural equation modeling (SEM) indicated that poor academic performance was linked to lower student engagement and that lower student engagement was associated with worse emotional well-being, confirming the concurrent validity of the scale. The results validate the integrated measure of engagement as a comprehensive assessment of student engagement in Portuguese adolescents.